Analysis of germination curves of cinchona officinalis L. (Rubiaceae) using sigmoidal mathematical models - Quiñones Huatangari, Lenin (2023)
Seed germination is the fundamental phenomenon that determines the successful growth and development of each plant species,even more so in Cinchona ofcinalis, which is a forest species that stands out for its medicinal importance. Te objective of thiswork was to determine the best sigmoidal mathematical model describing the germination of C. ofcinalis. For the germinationtest, a completely randomized design was used with six treatments and three replicates per treatment; 100 °C. ofcinalis seeds wereused per replicate, and 1800 seeds were needed in the trial. Gompertz sigmoidal, logistic, and von Bertalanfy models were used toanalyse the germination curves of C. ofcinalis. Te results of these adjustments were analysed based on the graphic representationand statistical criteria (Akaike’s value (AIC), R2 , and R2ai). Te results suggest that the Gompertz and logistic models havea better graphic representation, showing values close to those observed, while the von Bertalanfy model shows negative ger-mination values. According to the statistical criteria, the lowest AIC and the highest were obtained. R2 and R2ai with the Gompertzmodel, followed by the logistic model and von Bertalanfy. It is concluded that the Gompertz model can represent the shape of thegermination curves of C. ofcinalis for the six treatments of the test.